A Simple Model Established by Blood Markers Predicting Overall Survival After Radical Resection of Pancreatic Ductal Adenocarcinoma - Zhang, Li-xiang; Chen, Lei; Xu, A-Man (Frontiers in Oncology, 2020)
The prognostic prediction after radical resection of pancreatic ductal adenocarcinoma (PDAC) has not been well established. We aimed to establish a prognostic model for PDAC based on a new score system, which included another clinical routine serum marker. 438 patients who underwent curative PDAC at the First Affiliated Hospital of Anhui Medical University from January 2007 to January 2014 were included in this study. Univariate and multivariate analysis were used to screen for prognostic risk factors. We constructed the nomogram based on Cox proportional hazard regression models. The construction of the new score models was analyzed by receiver operator characteristic curve (ROC curve) and then was compared with other clinical indexes. Multivariate analysis showed that TNM stage, CA199, CEA, globulin, NLR and LMR were independent prognostic factors. The new score system had a higher AUC value than other risk factors, and the C-index of the nomogram was highly consistent for evaluating survival of PADC patients in the validation groups and training group. For the patients with PDAC after radical surgery, we developed a precise model to predict the prognosis based on the serum markers and other clinical indicators. For surgeons and patients, this score system can be effective help.